Insatiable appetite : the United States and the ecological degradation of the tropical world - Tucker, Richard P., 1938- (Berkeley : University of California Press, 2000)
This text presents a history of the transformation of the tropics in modern times, pointing ultimately to the declining biodiversity that has resulted from the domestication of widely varied natural systems.
America's sweet tooth: the sugar trust and the Caribbean lowlands -- Lords of the Pacific: sugar barons in the Hawaiian and Philippine islands -- Banana republics: yankee fruit companies and the tropical American lowlands -- The last drop: the American coffee market and the hill regions of Latin America -- The tropical cost of the automotive age: corporate rubber empires and the rainforest -- The crop on hooves: yankee interests in tropical cattle ranching -- Unsustainable yield: American foresters and tropical timber resources.
Includes bibliographical references (pages 437-524) and index.
Print version record.
JSTOR
Keywords: Tropical crops -- Economic aspects -- History -- 20th century; Tropical crops -- Environmental aspects -- History -- 20th century; Investments, American -- Tropics -- History -- 20th century; Environmental degradation -- Tropics -- History -- 20th century; Tropical Climate; Environment; Cultures tropicales -- Aspect économique -- Histoire -- 20e siècle.; Cultures tropicales -- Aspect de l'environnement -- Histoire -- 20e siècle.; Environnement -- Dégradation -- Régions tropicales -- Histoire -- 20e siècle.; NATURE -- Natural Resources; BUSINESS & ECONOMICS -- Environmental Economics; BUSINESS & ECONOMICS -- Green Business; HISTORY -- United States -- General; Environmental degradation; Investments, American; Tropical crops -- Economic aspects; Tropics; Ontbossing; Ecologische aspecten; Verenigde Staten; Ontwikkelingslanden; 1900-1999; Samfundsvidenskab -- Økonomi; History